Preclinical evaluation of [111In]MICA‐401, an activity‐based probe for SPECT imaging of in vivo uPA activity. (24th August 2016) - Vangestel, Christel; Thomae, David; Van Soom, Jeroen; Ides, Johan; wyffels, Leonie; Pauwels, Patrick; Stroobants, Sigrid; Van der Veken, Pieter; Magdolen, Viktor; Joossens, Jurgen; Augustyns, Koen; Staelens, Steven
Abstract : Urokinase‐type plasminogen activator (uPA) and its inhibitor PAI‐1 are key players in cancer invasion and metastasis. Both uPA and PAI‐1 have been described as prognostic biomarkers; however, non‐invasive methods measuring uPA activity are lacking. We developed an indium‐111 ( 111 In)‐labelled activity‐based probe to image uPA activity in vivo by single photon emission computed tomography (SPECT). A DOTA‐conjugated uPA inhibitor was synthesized and radiolabelled with 111 In ([ 111 In]MICA‐401), together with its inactive, hydrolysed form ([ 111 In]MICA‐402). A biodistribution study was performed in mice (healthy and tumour‐bearing), and tumour‐targeting properties were evaluated in two different cancer xenografts (MDA‐MB‐231 and HT29) with respectively high and low levels of uPA expression in vitro, with either the active or hydrolysed radiotracer. MicroSPECT was performed 95 h post injection followed by ex vivo biodistribution. Tumour uptake was correlated with human and murine uPA expression determined by ELISA and immunohistochemistry (IHC). Biodistribution data with the hydrolysed probe [ 111 In]MICA‐402 showed almost complete clearance 95 h post injection. The ex vivo biodistribution and SPECT data with [ 111 In]MICA‐401 demonstrated similar tumour uptakes in the two models: ex vivo 5.68 ± 1.41%ID/g versus 5.43 ± 1.29%ID/g and in vivo 4.33 ± 0.80 versus 4.86 ± 1.18 for MDA‐MB‐231 and HT‐29 respectively. Human uPA ELISA and IHC showed significantly higher uPA expression in the MDA‐MB‐231 tumours, while mouse uPA staining revealed similar staining intensities of the two tumours. Our data demonstrate non‐invasive imaging of uPA activity in vivo, although the moderate tumour uptake and hence potential clinical translation of the radiotracer warrants further investigation. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : A DOTA‐conjugated uPA activity‐based probe was synthesized and radiolabelled with 111 In ([ 111 In]MICA‐401), together with its inactive, hydrolysed form ([ 111 In]MICA‐402), and evaluated in cancer xenograft models with distinct in vitro uPA expression. Our data demonstrate the non‐invasive imaging of uPA activity in vivo ; however, moderate tumour uptake and potential clinical translation of the radiotracer warrant further investigation.